A competitive ligand-binding assay for the detection of neutralizing antibodies against dostarlimab (TSR-042) - Xiaolong Tom Zhang; Hong Chen; Weiping Shao; Zhongping John Lin; Murad Melhem; Sharon Lu (SpringerOpen, 2021)
Abstract Dostarlimab is a humanized anti-PD-1 monoclonal antibody. Dostarlimab (JEMPERLI; TSR-042) was recently approved in the USA and in the EU. The presence of neutralizing antibodies (NAbs) is a cause for concern because they block the therapeutic function of the antibody and reduce drug efficacy. Therefore, programs developing therapeutic biologics need to develop and validate assays that adequately assess the presence of NAbs in the serum of patients treated with biologic therapies. Presented here is the development and validation of a competitive ligand-binding assay that specifically detects anti-dostarlimab NAbs in human serum. Precision, sensitivity, hook effect, selectivity, assay robustness, stabilities, and system suitability were evaluated. In addition, drug tolerance of the assay with the implementation of a drug removal process was investigated. The cut point factor for the detection of NAbs in human serum at a 1% false-positive rate was determined. The assay's precision, sensitivity, hook effect, selectivity, robustness, and drug interference were tested and found to be acceptable. With system suitability and stability established, this assay has been used to evaluate NAbs to guide the development of dostarlimab. Trial registration: Clinicaltrials.gov, NCT02715284 . Registered 9 March 2016